Identification of risk factors in business valuation - Muhammad Najib Mohamed Razali; Rohaya Abdul Jalil; Kamalahasan Achu; Hishamuddin Mohd Ali (Journal of Risk and Financial Management, 2022)
It is widely accepted that risk and uncertainty are integral parts of the property valuation process. Uncertainty in property valuation is derived from the characteristics of property itself. The issue pertaining to risk and uncertainty in property valuations is currently one of the key concerns in global valuation practice to date in addressing the decision of risk and uncertainty in valuation, especially for business purposes or in the current term known as business valuation. The judgment and experience still depend on the expertise of the individual valuers alone. The valuation methods used can cause problems if certain elements in business such as risk are highlighted, especially to determine market value. There is a need for valuers to express assumptions which take into account risk and uncertainties, and then pass on the results of the estimation process to the end user of the valuation report. This research employed Analytical Hierarchical Process (AHP) to identify the level of risk in business valuation for valuers to identify which risk areas will expose them to professional liabilities, which then leads to mitigation of risk to determine value in business valuations. AHP will also be able to identify the level of risk in each of the approaches in business valuation which could help valuers to determine the value and market value in the valuation process. This paper will propose some practical approaches of how to address the risk and uncertainty of the valuation process, especially for the purpose of business valuation.
Keywords: 650; AHP; business; risk; valuation